Edukasi tentang 1000 hari pertama kehidupan dalam meningkatkan pengetahuan dan sikap calon pengantin laki-laki - Betty Yosephin Simanjuntak; Anang Wahyudi (AcTion: Aceh Nutrition Journal, 2021)
The preconception period is the ideal time to optimize the health of women before becoming a mother. The prevalence of stunting is still above 25%, which will affect the next life cycle. The objective of this study was to assess the knowledge and attitudes of fathers through educational nutrition during preconceptions. It was designed as a quasi-experimental study. There were a total of 60 participants in the leaflet group and 60 participants in pocketbooks with incidental sampling technique. Education of first thousands of days of life which contain chronic energy deficiency (CED), anaemia, initiation of breastfeeding, exclusive breastfeeding, weaning food and stunting topics was given by officer of Religious Affairs Office for three days.  Data were collected using a structured questionnaire through interviews. Data analysis was used pair t-test, Wilcoxon and Mc Nemar test. Results, after getting education using pocketbook, increasing knowledge especially at CED and weaning food (p= 0,006), anaemia, early initiation of breastfeeding and stunting (p= 0,000), exclusive breastfeeding (p= 0,035). Increasing in attitudes significantly after using pocketbooks especially (p < 0,05) on CED, anaemia and initiation of breastfeeding, exclusive breastfeeding, and stunting topics. In conclusion, the increase in men's knowledge in the leaflet group, especially anaemia and initiation of breastfeeding while in the pocketbook group all of the topics increased significantly.